Landscape Layout in Taman Tugu Suharto Semarang by Implementing Green City Development (P2KH) - Isna Pratiwi; Dimas Wicaksono; Retno Mayasari; Azzah Balqis Sabbah (Litbang Pemas - Universitas Islam Lamongan, 2021)
City Parks as open spaces in urban areas should function as spaces for the interaction of city residents for various useful activities, functions, and interests. The existence of open space is an important element that can maintain the ecological sustainability of a city. Taman Tugu Suharto is located in Kelurahan Bendan Duwur, Semarang, a place marked by an 8- meter high monument, which is the meeting point between Kaligarang and Kali Kreo. At the turn of the Javanese New Year (1 sura), people perform kungkum rituals (is a kind of rituals for local people to bathe in the river) they believe, with the kungkum ritual on the night of 1 Sura, they will always get blessings and safety in the future and their wishes will be granted. Taman Tugu Suharto is one of the parks in Semarang that is unique and has the potential to be developed into a tourist attraction, especially to support the Green City in Semarang. This study aims at designing Taman Tugu Suharto. This park is belonging to the City Government has several obstacles, such as the unorganized park area, the absence of adequate facilities, difficult access from the riverbank to the Tugu Suharto, the limitate of the parking area, and little attention of the government to develop this area. So far, people rarely visit and use the park for purpose of recreation. Taman Tugu Suharto using 8 (eight) attributes the Green City such as green planning, green design, green community, green space, green building, green energy, green transportation, green water, and green waste. These attributes, are used as a reference in planning or developing city parks and developing more comfortable city parks that fulfill the Green Space standards in Semarang. Therefore, it is necessary to develop a landscape layout design appropriately so that it can be utilized optimally and sustainably by Semarang citizens.